Dampak Combine harvester Terhadap Penyerapan Tenaga Kerja dan Pendapatan Petani Padi Sawah Di Kecamatan Indrapuri Kabupaten Aceh Besar - Faradilla Janah HT; Zakiah Zakiah; Agustina Arida (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The use of modern tools or machines can save time and reduce the number of workers compared to traditional agricultural systems. The history of the world of agriculture has increased from traditional agriculture to modern agriculture accompanied by technological developments. As for one of the advanced machines in the rice harvesting process that is currently popular in recent years, the Combine harvester. Combine harvester is a rice harvesting machine that can cut grain, thresh, and clean grain. Indrapuri Sub-district is one of the sub-districts in Aceh Besar District that has carried out agricultural mechanization, as evidenced by the amount of use of agricultural equipment or machinery in this sub-district, which distinguishes it from other sub-districts. This study aims to determine the impact of the use of harvesting equipment (Combine harvester) on labor absorption and its effect as well as differences in income between farmers Combine harvester and non-Combine harvester. The analysis technique used in this research is descriptive technique, simultaneous equation (Two Stage Least Square) and different test (Independent Sample T test). The results of the study show that the impact of using a harvester (Combine Harvester) on the absorption of labor from 45 days/labor to 3 days/labor. The results of the 2SLS (Two Stage Least Square) test show that simultaneously and partially the farmer's income variable (Fincome) is influenced by the production variable (Yrice), harvesting costs (Hc) and dummy combine (Dc) with an R-square value of 99.3% while the remaining 0.7% is influenced by other variables not examined. The results of the different test ((Independent Sample T Test) show that there is a difference in income between farmers using Combine harvesters and farmers using non-combine harvesters of Rp.4,988.041, which means that the income of farmers using Combine harvesters is greater than that of non-combine harvesters, so that the use of tools Combine harvester harvest has a positive impact on the income of user farmers.